The impact of sublethal antimicrobial blue light on lipidomic changes of Escherichia coli and Salmonella Typhimurium - Wu, Jiaxin; Lu, Xuan; Huang, Ming; Wu, Shuyan; Zeng, Maomao; Liu, Zhaojun; Yu, Keyang; Zhang, Xiujuan; Sun, Xiaoying; Wang, Xiaoyuan; Hu, Xiaoqing (Frontiers in Cellular and Infection Microbiology, 2025)
Antimicrobial blue light (aBL) is an effective non-thermal disinfection method against foodborne bacterial pathogens. While aBL-induced oxidative stress is known to cause cell membrane damage, its specific effects on bacterial lipid composition remain poorly understood. This study investigated aBL-triggered lipidomic changes in two major foodborne pathogens (Escherichia coli and Salmonella Typhimurium). We identified more than 70 lipid species across 6 classes, with over 50% showing significant variations in profile, intensity, and degree of unsaturation following aBL exposure. Phosphatidylethanolamine (PE) species exhibited the most pronounced alterations. Notably, both strains demonstrated decreased unsaturated lipid intensity alongside increased malondialdehyde levels—a key oxidative stress marker. These findings provide crucial insights into bacterial lipid dynamics under aBL stress and advance our understanding of the molecular mechanisms behind aBL-mediated bacterial inactivation.